Intelligent decision support system in the face of uncertainty and risks in project management - Grinchenko, Marina; Rohovyi, Mykyta (Харківський національний університет радіоелектроніки, 2024)
In today's world, Scrum is the most popular approach to managing teams in software development. However, there are factors that influence the emergence of project risks, namely: inaccuracies in the formulation of tasks that the team evaluates and a low level of communication culture, as well as shortcomings in the procedures for distributing tasks among team members. An intelligent decision support system under conditions of uncertainty and risk in project management allows the project manager to provide mechanisms to reduce the impact of risks. The purpose of this study is to reduce the impact of risks associated with the perception of tasks from the tracking system and the distribution of tasks among team members within the project sprint to ensure the successful completion of the project. Key factors affecting the effectiveness of teamwork are analyzed and identified. An intelligent decision support system has been developed that integrates data from the tracking system and, using LLM and a stable matching algorithm, provides recommendations for describing project sprint tasks and distributing these tasks among performers.
Keywords: project; risk; project team; intelligent system